QUALIDADE DAS ÁGUAS SUBTERRÂNEAS DA REGIÃO DE MARCO E BELA CRUZ - CEARÁ - Teixeira, Zulene Almada; Cavalcante, Itabaraci N.; Vasconcelos, Maria Kátia de; Frangipani, Alcide; Vasconcelos, Sônia Maria S. (Águas Subterrâneas, 2001)
Resumo não disponível.